Prescription Patterns and Antimicrobial Susceptibility in Complicated Urinary Tract Infection at a North Indian Tertiary Care Hospital: A Descriptive Study - Dr. Anuj Pareek; Dr. Purooshottam; Dr. Uma Advani; Dr. harshil patel (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background Complicated urinary tract infection (cUTI) increases morbidity, length of stay and antimicrobial resistance. Indian data on real world prescribing and susceptibility trends remain limited . Methods A hospital based descriptive study (March 2023 – Feb 2024) enrolled 100 consecutive adults admitted with cUTI to the Urology ward of a 2200 bed tertiary hospital. Demographics, comorbidities, prescriptions (admission, culture directed, discharge) and adverse drug reactions (ADRs) were captured prospectively on a structured pro forma. World Health Organization (WHO) prescribing indicators were applied. Isolates underwent standard CLSI urine culture and antimicrobial susceptibility testing. Data were analysed with SPSS v16 using descriptive statistics and χ² as appropriate. Results Mean age was 45.7 ± 17.0 years; 90 % were male. Stones (45 %) and hydronephrosis (38 %) were common risk factors. Median drugs/prescription = 4 (IQR 3–5); all were generic and Essential Drug List compliant. Antimicrobial use was universal at admission; ceftriaxone (61 %) and amikacin (100 %) predominated. After culture, de escalation occurred in 43 % and carbapenems were initiated in 50 % of culture guided regimens. Escherichia coli (56.7 %) and Klebsiella spp. (10.2 %) were leading pathogens. Overall susceptibility (%) was highest for colistin (94), nitrofurantoin (84) and piperacillin tazobactam (77); fluoroquinolone resistance exceeded 60 %. Thirty three patients (33 %) experienced ≥ 1 ADR, most commonly dyspepsia and headache with diclofenac/paracetamol or pantoprazole; no serious ADRs occurred. Conclusion High third generation cephalosporin and aminoglycoside use with limited culture directed de escalation was observed. Rising fluoroquinolone resistance underscores the need for protocol driven, carbapenem sparing stewardship. Continuous surveillance and clinician feedback can optimise empirical choices and curb resistance.